The sources of the immigrant-native wage gap: worker, firm and job title heterogeneity - Severino, Madalena Guerreiro Leal (2022)
I investigate the role of worker, firm, and job title heterogeneity in the immigrant-native wage gap. Using matched employer-employee data, I estimate the conditional wage gap based on a high-dimensional fixed effects model and apply Gelbach’s decomposition method. Results indicate that the earnings differential between immigrants and natives is more salient within firms (across job titles), rather than between firms. Nonetheless, almost half of the wage penalty rests on workers’ unobserved characteristics, possibly linked to imperfect human capital transferability or other personal skills besides formal education. I further conclude that the immigrant-native wage gap is greater at the extremes of the earnings distribution.